2015
DOI: 10.1002/celc.201402410
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Reduction of Alkyl Monohalides at Silver in Dimethylformamide: Effects of Position and Identity of the Halogen

Abstract: Electrochemical reduction of primary (1‐halodecane), secondary (2‐halohexane and cyclohexyl halide), and tertiary halides (tert‐butyl halide) at a silver cathode in dimethylformamide (DMF) containing 0.050 M tetramethylammonium perchlorate (TMAP) was investigated with the aid of cyclic voltammetry and controlled‐potential (bulk) electrolysis for iodides, bromides, and chlorides. Selected reductions were probed in dried DMF–TMAP and DMF containing tetra‐n‐hexylammonium perchlorate (THAP). Cyclic voltammograms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…We attribute this potential shift to the well-known catalytic effects of silver as a cathode material for carbon-chlorine bond cleavage, as reported in literature. [18][19][20][21][22][23][24][25] It is interesting that there is little shift in the peak potential for the second stage of reduction when glassy carbon is compared with silver; furthermore, the third and fourth cathodic peak potentials are independent of cathode material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute this potential shift to the well-known catalytic effects of silver as a cathode material for carbon-chlorine bond cleavage, as reported in literature. [18][19][20][21][22][23][24][25] It is interesting that there is little shift in the peak potential for the second stage of reduction when glassy carbon is compared with silver; furthermore, the third and fourth cathodic peak potentials are independent of cathode material.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] Recently, it has been shown in our laboratory that the position and identity of the halogen atom affect the reduction potential and mechanism. 21,22 Research from the groups of Isse 23,24 and Amatore 25 has provided further insight concerning the mechanisms of electroreductive carbon-chlorine bond cleavage at silver cathodes; it has been determined that activated species adsorb onto the silver surface, thereby promoting the observed catalytic effects. In the present work, cyclic voltammetry and controlled-potential (bulk) electrolysis have been used to investigate the electrochemical reduction of methoxychlor at carbon and silver cathodes in DMF containing 0.050 M tetra-n-butylammonium tetrafluoroborate (TBABF 4 ) as supporting electrolyte.…”
mentioning
confidence: 99%
“…As part of a recent investigation of the direct electrochemical reduction of a selected group of primary, secondary, and tertiary alkyl halides at silver cathodes in dimethylformamide containing tetramethylammonium perchlorate, our laboratory explored briefly the behavior of cyclohexyl bromide ( 1 ) and cyclohexyl iodide ( 2 ) and found that the electrolysis products consist of a mixture of cyclohexane, cyclohexene, and bicyclohexyl. To the best of our knowledge, no detailed study of the behavior of these two secondary alicyclic halides at any cathode material (including vitreous carbon) has been previously conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report that silver exhibits a remarkable catalytic activity towards the electroreductive dehalogenation of organic halides by Mussini, numerous organic chlorides have been tested, further confirming the catalytic property of Ag in triggering the C−Cl bonds breakage . Peters and coauthors have made significant contributions to the understanding of the voltammetric properties of various organic chlorides (mainly chlorinated pesticides and refrigerants) at Ag electrode and the possibility of complete dechlorination of these compounds by bulk electrolyses . In general, the extraordinary catalytic activity of Ag is primarily attributed to its high affinity with chlorine (ion), making itself distinct with other metals, and its catalytic property is so very important in the DET process.…”
Section: Critical Factors For Controlling the Electroreductive Dehalomentioning
confidence: 87%
“…In recent years, it has been shown that the electroreductive dehalogenation of organic chlorides is controlled by many factors, such as the nature of electrode materials, the molecular structure of organic chlorides, the solvent chemistry and the applied potentials, etc . We now focus on the critical factors of the dechlorination reaction, in order to better understand the mechanisms of electroreductive dehalogenation.…”
Section: Critical Factors For Controlling the Electroreductive Dehalomentioning
confidence: 99%